Latin America and the Caribbean vis-à-vis regional coordination - Arriola, Salvador (2000)
Reflects on how the countries of Latin America and the Caribbean remain disunited in spite of having established appropriate mechanisms, such as SELA, to deal with regional consultation and coordination.